2020
DOI: 10.1371/journal.pone.0232475
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of neurological impairments in myalgic encephalomyelitis/ chronic fatigue syndrome using neuroimaging techniques

Abstract: Background Myalgic encephalomyelitis/ Chronic Fatigue Syndrome (ME/CFS) is a multi-system illness characterised by a diverse range of debilitating symptoms including autonomic and cognitive dysfunction. The pathomechanism remains elusive, however, neurological and cognitive aberrations are consistently described. This systematic review is the first to collect and appraise the literature related to the structural and functional neurological changes in ME/ CFS patients as measured by neuroimaging techniques and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 75 publications
(511 reference statements)
1
52
0
1
Order By: Relevance
“…Suggestions are (i) immunological mechanisms such as overexpression of pro-inflammatory cytokines, (ii) metabolic dysregulation, (iii) diffuse axonal damage, (iv) fatigability due to reduced plasticity of the MS brain, or (v) neuropsychological influences [ 6 , 7 , 8 ]. Functional MRI studies revealed different areas of cortical activation in fatigued MS patients as compared to non-fatigued patients, indicating different functional patterns in both groups [ 9 , 10 ]. The question if biomolecules—and if yes, which ones—play crucial roles in the pathogenesis of MS fatigue is still unanswered [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Suggestions are (i) immunological mechanisms such as overexpression of pro-inflammatory cytokines, (ii) metabolic dysregulation, (iii) diffuse axonal damage, (iv) fatigability due to reduced plasticity of the MS brain, or (v) neuropsychological influences [ 6 , 7 , 8 ]. Functional MRI studies revealed different areas of cortical activation in fatigued MS patients as compared to non-fatigued patients, indicating different functional patterns in both groups [ 9 , 10 ]. The question if biomolecules—and if yes, which ones—play crucial roles in the pathogenesis of MS fatigue is still unanswered [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the identification of acceptable objective markers of ME/CFS which can be utilised in epidemiological research in Europe is of very high priority. On this question, differences between ME/CFS cases and controls have been observed in the brain (structure, function, and metabolites), cognitive function and sleep function [37][38][39]. Associations between the occurrence of ME/CFS clinical symptoms, HHV−6, HHV−7 and B19 infection/co-infection reactivation, and increased expression levels of TNF-α and IL6 [40] have been observed, as well as alterations in the levels of infection markers of B19V [41] and EBV [42].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review on CFS and cerebral blood flow found inconsistencies in the published results 5 . We have not identified studies showing that high‐dose thiamine can increase the cerebral blood flow in humans.…”
mentioning
confidence: 82%
“…Elevated cerebral lactate levels in patients with CFS were reported in several studies 5 . High‐dose thiamine treatment has been shown to activate the pyruvate dehydrogenase complex, catalysing decarboxylation of pyruvate, and reduce lactate concentrations in patients with congenital lactic acidaemia 6 …”
mentioning
confidence: 98%